2021
DOI: 10.1128/mra.00303-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Three Clinical Listeria monocytogenes Sequence Type 8 Strains from Recent German Listeriosis Outbreaks

Abstract: We report here the closed genome sequences of three clinical Listeria monocytogenes strains of multilocus sequence typing (MLST) sequence type 8 (ST8). These strains are representatives of three separate listeriosis outbreak clusters (Alpha1, Pi4, and Sigma1) that affected Germany between 2012 and 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The remaining seven strains, mainly recovered from RTE food, were grouped into three CCs, with single isolates in each ( Figure 1 ). L. monocytogenes of the CCs identified in the present study were also previously detected among 100 strains of IIa serogroup recovered from food but were also often isolated from humans with listeriosis [ 12 , 14 , 18 , 44 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The remaining seven strains, mainly recovered from RTE food, were grouped into three CCs, with single isolates in each ( Figure 1 ). L. monocytogenes of the CCs identified in the present study were also previously detected among 100 strains of IIa serogroup recovered from food but were also often isolated from humans with listeriosis [ 12 , 14 , 18 , 44 , 45 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 78%
“…The remaining seven strains, mainly recovered from RTE food, were grouped into three CCs, with single isolates in each (Figure 1). L. monocytogenes of the CCs identified in the present study were also previously detected among 100 strains of IIa serogroup recovered from food but were also often isolated from humans with listeriosis [12,14,18,[44][45][46][47]. Further analysis of WGS sequences revealed that all 100 current isolates were classified into eight sequence types, with the most prevalent ST155 (33; 33.0%), ST121 (30; 30.0%), and ST8 (28; 28.0%) (Figure 2).…”
Section: Wgs-based Typing Of L Monocytogenes Of Iia Serogroupsupporting
confidence: 57%
See 1 more Smart Citation
“…The Ny9 outbreak was caused by a ST394 clone. Genetic and phenotypic analysis demonstrated that this clone possessed a very similar virulence potential like the Sigma1 outbreak strain ( 22 , 46 ), which was one of the closest relatives in our strain collection. ST394 strains have not been described so far in the context of large outbreak clusters.…”
Section: Discussionmentioning
confidence: 78%
“…This selection included strain 18-04540 from the large Epsilon1a outbreak (18) as a representative for ST6 with average MFL/NL risk (Fig. 3D), strain 21-03201 from the Alpha10 cluster representing hypervirulent ST1, strain 19-05816 from the Pi4 cluster (40) for hypovirulent ST8, strain 19-06323 (Chi1a cluster) as a hypovirulent ST14 isolate, the sporadic 21-04322 strain representing hypovirulent ST29 and the Omikron1 strain 17-01049 as a member of hypovirulent ST155.…”
Section: In Vitro Strain Virulence Corresponds To Risk Potential Of H...mentioning
confidence: 99%